Combined Plyometric and Short Sprint Training in U-15 Male Soccer Players: Effects on Measures of Jump, Speed, Change of Direction, Repeated Sprint, and Balance - Aloui, Ghaith; Hermassi, Souhail; Bartels, Thomas; Hayes, Lawrence D.; Bouhafs, El Ghali; Chelly, Mohamed Souhaiel; Schwesig, René (Frontiers in Physiology, 2022)
This project investigated the effect of incorporating 8 weeks of biweekly combined plyometric and short sprints training into the in-season regimen of youth male soccer players. Participants were randomly allocated to an experimental group (n = 17, age: 14.6 ± 0.5 years, body mass: 60.5 ± 7.1 kg, height: 1.64 ± 0.08 m, body fat: 11.3 ± 1.4%) and a control group (n = 17, age: 14.6 ± 0.4 years, body mass: 61.0 ± 3.9 kg, height: 1.67 ± 0.05 m, body fat: 11.8 ± 1.4%). Measures obtained pre- and post-intervention included vertical and horizontal jump performance (i.e., squat-jump [SJ], countermovement-jump with aimed arms [CMJA], and five-jump test [FJT]), and sprint performance (i.e., 10-m and 30-m sprint). In addition, Measures obtained pre- and post-intervention included change-of-direction ability (sprint with 90° Turns [S90°] and sprint 9–3–6–3–9 m with backward and forward running [SBF]), repeated shuttle sprint ability (RSSA), and dynamic balance performance (Y balance test). The training group experienced superior jump (all p < 0.05; d ≥ 0.71), sprint (all p < 0.05; d ≥ 0.64), change-of-direction ability (all p < 0.05; d ≥ 0.66), RSSA (all parameters except the fatigue index p < 0.01; d ≥ 0.71), and dynamic balance (all p ≤ 0.05; d ≥ 0.50) improvement. Adding biweekly combined plyometric and short sprints training to standard training improves athletic performance of youth male soccer players (U15).